Convection Type Electric Stove with Air Ionization - Romanchikov S. (Техника и технология пищевых производств)
Increasing the efficiency of electric stoves currently remains an unsolved problem. The present study proposes a new design scheme for the electric convection stove with an air ionization device (Electric Stove PE-UIEV). This will reduce energy costs and speed up the cooking process. The stove in question is based on the method of electrothermal convection of heat-exchange surfaces of the frying deck. The proposed design reduces the formation of carcinogenic substances and improves the taste of fried and stewed dishes. The improved device increases the heat transfer coefficient from the burner surface to the cooker by 3 times since it creates better conditions for electrothermal convection. Treating air with electricity gives it adhesive properties: the air sticks to grounded surfaces of boilers. Ionized air intensively performs the function of heat carrier. Ionization reduces carcinogenic substances by 2–4 times and disinfects of ready-made dishes. The practical significance of the technical solution lies in the fact that the proposed design reduces the load on the ventilation and air conditioning system. In addition, the stove can be used for cooking in restricted (closed) spaces, and it improves the taste quality indicators. Unlike other stoves, this one reduces hot air circulation and, thus, its losses.